Faktor-Faktor yang Memengaruhi Orang Tua dalam Memilih Sekolah TK bagi Anak - Boking, Agnes Juliet; Srinadi, I Gusti Ayu Made; Suciptawati, Ni Luh Putu (Jurnal Matematika; Vol 3 No 2 (2013), 2013)
School was second place for children to get knowledge and develop skills or talents. A great school and accordance with the character of the child will be able to guide children toward a better future. There are many factors that influence parents in choosing a kindergarten school for children affected from both the internal parents, schools or internal environment. The author would like to see the factors that influence whether parents in choosing a kindergarten school for children and whether there is a relationship between internal indicators of parents, school internally, and the environment. Internal indicators of parents, school internally, and the environment in question include: parent education, parental employment, parental income, school programs, teacher background, facilities, location, promotion, reputation, cost, references, traditions, parents and the learning process. The analysis used were factor analysis and canonical correlation analysis. The results showed that there are seven factors that influence parents in choosing a kindergarten school which factors socio-economic background of parents, location, teacher backgroud, school status, environment, state school, and cost factors. Result of canonical correlation analysis showed that between internal indicators parent with internal school, among parents with the internal environment, and the relationshipbetween internal school and environment provides each significant effect.
Keywords: Schools; Internal Indicators Parents; Internal School; Environment; Factor Analysis; Canonical Correlation Analysis